Balancing the management of powerline right-of-way corridors for humans and nature. (15th March 2023) - Garfinkel, Megan; Hosler, Sheryl; Roberts, Michael; Vogt, Jess; Whelan, Christopher; Minor, Emily
Abstract: Green space in electric powerline rights of way (ROWs) can be a source of both ecosystem services and disservices in developed landscapes. Vegetation management within the ROW may influence tradeoffs that maximize potential services or disservices. Frequently mowed ROWs managed as lawn harbor less biodiversity than ROWs with taller vegetation, but may be preferred by people for aesthetic reasons and because they provide space for recreational activities. We conducted a survey of residents living by ROWs in the Chicago, Illinois USA metropolitan area to determine if residents prefer ROWs managed as lawn over those managed as native prairies or allowed to grow freely with only woody vegetation removed ("old-field ROWs"). We found that respondents did not prefer mowed over prairie or old-field ROWs. Furthermore, respondents living near mowed ROWs were least likely to think that the ROW is attractive, while those living near prairie ROWs were most likely to. Survey respondents tended to believe it was important for ROWs to provide habitat for wildlife, and wildlife observation was the most frequently reported activity conducted in the ROW. Finally, we found that a respondent's perception of biodiversity in the ROW was more closely correlated with positive feelings about the ROW than measured biodiversity levels. Our results suggest that managing ROWs for wildlife habitat is fully compatible with managing them for human enjoyment. We therefore recommend that where possible, ROW vegetation is managed in a more "natural" way than lawn because it has the potential to benefit both wildlife and people. Graphical abstract: Image 1 Highlights: We used surveys to compare attitudes towards Rights-of-Ways managed in three ways. Residents tend to find lawn ROWs less attractive than prairie or old-field ROWs. Most respondents believe it is important that ROWs provide habitat for wildlife. Perceived rather than measured biodiversity predicted feelings towards the ROW. Managing ROWs for wildlife habitat is compatible with managing for human enjoyment.